Step up to the plate, Maria Singh - Krishnaswami, Uma, 1956- (Tu Books, an imprint of Lee & Low Books, 2017)
When World War II erupts in the spring of 1945, nine-year-old Maria Singh begins practicing her pitching, just in time for her teacher to form the first-ever girls' softball team in Yuba City, California, while her parents struggle trying to stay on their farm.